Drosophila microRNAs exhibit diverse spatial expression patterns during embryonic development - Aboobaker, A.A; Tomancak, P; Patel, N; Rubin, G.M; Lai, E.C (Proceedings of the National Academy of Sciences - PNAS, 2005)
MicroRNAs (miRNAs) are an extensive class of regulatory RNA whose specific functions in animals are generally unknown. Although computational methods have identified many potential targets of miRNAs, elucidating the spatial expression patterns of miRNAs is necessary to identify the sites of miRNA action. Here, we report the spatial patterns of miRNA transcription during Drosophila embryonic development, as revealed by in situ hybridization to nascent miRNA transcripts. We detect expression of 15 "stand-alone" miRNA loci and 9 intronic miRNA loci, which collectively represent 38 miRNA genes. We observe great variety in the spatial patterns of miRNA transcription, including preblastoderm stripes, in aspects of the central and peripheral nervous systems, and in cellular subsets of the mesoderm and endoderm. We also describe an intronic miRNA (miR-7) whose expression pattern is distinct from that of its host mRNA (bancal), which demonstrates that intronic miRNAs can be subject to independent cis-regulatory control. Intriguingly, the expression patterns of several fly miRNAs are analogous to those of their vertebrate counterparts, suggesting that these miRNAs may have ancient roles in animal patterning.